2021
DOI: 10.3389/fpsyg.2021.710470
|View full text |Cite
|
Sign up to set email alerts
|

Cross- and Within-Domain Associations of Early Reading and Mathematical Skills: Changes Across the Preschool Years

Abstract: Existing research has mainly examined the role of cognitive correlates of early reading and mathematics from a stationary perspective that does not consider how these skills unfold and interact over time. This approach constraints the interpretation of cross-domain associations and the specificity of domain-specific covariates. In this study, we disentangle the role of these predictors and investigate cross-domain associations between reading, math, and two related domain-specific predictors (phonological awar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 101 publications
(130 reference statements)
0
1
0
Order By: Relevance
“…Various studies have demonstrated a strong correlation between reading and math (e.g., Brock et al, 2018;Chu et al, 2016;Cirino et al, 2018;Davis et al, 2014;Hecht et al, 2001;Huo et al, 2021;Korpipää et al, 2017Korpipää et al, , 2019Kwok et al, 2021;Landerl & Kolle, 2009;Lerkkanen et al, 2005;Markowitz et al, 2005;Peters et al, 2020;Willcutt et al, 2013). For example, children with mathematical learning disabilities are often found to have reading difficulties (Landerl & Kolle, 2009;Willcutt et al, 2013).…”
mentioning
confidence: 99%
“…Various studies have demonstrated a strong correlation between reading and math (e.g., Brock et al, 2018;Chu et al, 2016;Cirino et al, 2018;Davis et al, 2014;Hecht et al, 2001;Huo et al, 2021;Korpipää et al, 2017Korpipää et al, , 2019Kwok et al, 2021;Landerl & Kolle, 2009;Lerkkanen et al, 2005;Markowitz et al, 2005;Peters et al, 2020;Willcutt et al, 2013). For example, children with mathematical learning disabilities are often found to have reading difficulties (Landerl & Kolle, 2009;Willcutt et al, 2013).…”
mentioning
confidence: 99%